2022
DOI: 10.3390/jcm11030886
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of Hemoglobin to Red Cell Distribution Width: A Strong Predictor of Clinical Outcome in Patients with Heart Failure

Abstract: Background: Hemoglobin (Hb) is a standard and widely available clinical parameter that predicts clinical outcomes in heart failure (HF) patients. Red cell distribution width (RDW) is also a routinely measured clinical parameter that is predictive of clinical outcomes in HF. The ratio between Hb and RDW has yet to be evaluated in HF. Methods: We evaluated the predictive value of the Hb/RDW ratio on clinical outcomes in patients with HF. All patients diagnosed with chronic HF at a health maintenance organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
1
20
0
6
Order By: Relevance
“…A recent study reported an independent association between a low hemoglobin/RDW ratio and the risk of death as well as the combined endpoint of death or cardiovascular hospitalization in a cohort of 6888 HF patients. Interestingly, this association was observed over the whole spectrum of HF types, including HFrEF and HFpEF [ 38 ].…”
Section: Rdw Change In Heart Failurementioning
confidence: 99%
“…A recent study reported an independent association between a low hemoglobin/RDW ratio and the risk of death as well as the combined endpoint of death or cardiovascular hospitalization in a cohort of 6888 HF patients. Interestingly, this association was observed over the whole spectrum of HF types, including HFrEF and HFpEF [ 38 ].…”
Section: Rdw Change In Heart Failurementioning
confidence: 99%
“…There is increasing evidence that HRR is a new prognostic indicator in critically ill patients with malignant diseases. For example, Qin et al explored the nonlinear relationship between all-cause mortality and HRR value in patients with ischemic stroke [ 27 ], and Rahamim et al found that HRR was an important prognostic tool for predicting mortality in heart failure and the hospitalization of patients with cardiovascular disease [ 9 ]. Chi et al found that low HRR were associated with a dual risk of disease progression or cancer recurrence in patients and used them to predict poor prognosis in patients with cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the first measurement of vital signs and laboratory data within the first 24 hours of ICU admission was included in this study. The initially selected laboratory measurements included ethnicity, age, sex, pregnancy, abrosia, dialysis, heart rate (beats/minute), mean blood pressure (MBP, mmHg), respiratory rate (breaths/minute), temperature (°C), peripheral oxygen saturation (SpO 2 , %), Oxford Acute Severity of Illness Score (OASIS), Simplified Acute Physiology Score II (SAPSII), Logistic Organ Dysfunction System (LODS) score, SOFA score, GCS score, myocardial infarction, congestive heart failure, peripheral vascular disease, chronic pulmonary disease, diabetes, paraplegia, RDW (×10 9 /L), calcium (mg/dL), potassium (mmol/L), Hb (g/L), sodium (mmol/L), glucose (mg/dL), hematocrit (%), platelets (×10 9 /L), the Hb/RDW ratio (HRR) [ 9 , 18 , 19 ], chloride (mmol/L), prothrombin time (PT, seconds), white blood cell (WBC) count (×10 9 /L), anion gap (×10 9 /L), bicarbonate (mmol/L), creatinine (mEq/L), international normalized ratio (INR), norepinephrine, and vasopressin. ICU all-cause mortality referred to in-hospital survival and was used as the outcome of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects were also found in a higher level of hemoglobin, such as polycythemia, plateau residents and newborns [ 4 6 ]. Moreover, mortality and incidence of complications of cardiovascular disease in diabetic patients could be affected by hemoglobin concentration [ 7 ]. Collectively, hemoglobin concentration has become an important monitoring indicator of health status.…”
Section: Introductionmentioning
confidence: 99%